2014
DOI: 10.1037/a0033906
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the cycle of mistrust: Wise interventions to provide critical feedback across the racial divide.

Abstract: Three double-blind randomized field experiments examined the effects of a strategy to restore trust on minority adolescents' responses to critical feedback. In Studies 1 and 2, 7th-grade students received critical feedback from their teacher that, in the treatment condition, was designed to assuage mistrust by emphasizing the teacher's high standards and belief that the student was capable of meeting those standards--a strategy known as wise feedback. Wise feedback increased students' likelihood of submitting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
241
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 316 publications
(260 citation statements)
references
References 87 publications
8
241
2
1
Order By: Relevance
“…Preparatory interventions have a special importance because they provide students a first lens for making sense of events they later experience. However, how a professor introduces difficult course material, provides critical feedback, or responds to a struggling student; how a dean welcomes the entering class; and how a university frames an academic probation letter, among many other events, can have independent effects (27,28). These all represent opportunities to improve the psychological environment of college and thus student success.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preparatory interventions have a special importance because they provide students a first lens for making sense of events they later experience. However, how a professor introduces difficult course material, provides critical feedback, or responds to a struggling student; how a dean welcomes the entering class; and how a university frames an academic probation letter, among many other events, can have independent effects (27,28). These all represent opportunities to improve the psychological environment of college and thus student success.…”
Section: Discussionmentioning
confidence: 99%
“…The second was a critical feedback intervention. This emphasized that critical academic feedback from professors and other instructors reflects instructors' high standards and confidence students can meet those standards, not a negative judgment of the student or his or her potential (27). Survey.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast Bird et al (2017) and Chande et al (2015) found positive and sizable effects. Yet another intervention in this category is the wise feedback intervention in Yeager et al (2014c) which provided middle school children who were getting feedback on an essay with a note that their teacher held them to a 20 We note, however, that the use of fictional descriptions in general could raise ethical concerns about the possibility of manipulation and might also harm the credibility of those providing the information. 21 The affirmation treatment thus differed from the affirmation treatments discussed below because it included decriptions of older students' experiences.…”
Section: Social Belonging Identity Activation and Mindset Nudgesmentioning
confidence: 99%
“…This representation of the exercise and interactive elements draws on other successful social-psychological interventions (17)(18)(19)(20). Teachers were treated as experts and agents of positive change for others, not as recipients of remediation.…”
Section: Response or Themementioning
confidence: 99%